n → ∞ lim sin ( ( 2 + 3 ) n π + 6 π )
Does the limit above exist?
Bonus : Find the limit if it exists, or prove that it does not exist.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is just an approximate and intuitive way to solve this problem:
First, note that choosing a bigger integer value of n will result in a closer approximation of ( 2 + 3 ) n to an even integer. For example:
n | ( 2 + 3 ) n |
2 | 1 3 . 9 2 8 2 0 3 2 3 . . . |
3 | 5 1 . 9 8 0 7 6 2 1 1 . . . |
4 | 1 9 3 . 9 4 8 4 5 2 . . . |
5 | 7 2 3 . 9 9 8 6 1 8 8 . . . |
. . . | . . . |
As the value of ( 2 + 3 ) n get nearer to an even number when n increases, π ( 2 + 3 ) n can be approximated and treated like 2 k π (with k ∈ Z ) so that:
sin ( π ( 2 + 3 ) n + 6 π ) ≈ sin ( 2 k π + 6 π ) = sin ( 6 π ) = 2 1
⟹ n → ∞ lim sin ( π ( 2 + 3 ) n + 6 π ) = 2 1
Problem Loading...
Note Loading...
Set Loading...
Note that ( 2 + 3 ) n + ( 2 − 3 ) n = 2 0 ≤ m ≤ 2 1 n ∑ ( 2 m n ) 2 n − 2 m 3 m = 2 K n is an even integer, and hence sin ( ( 2 + 3 ) n π + 6 1 π ) = sin ( 2 K n π + 6 1 π − ( 2 − 3 ) n π ) = sin ( 6 1 π − ( 2 − 3 ) n π ) Since 0 < 2 − 3 < 1 we deduce that ( 2 − 3 ) n → 0 as n → ∞ , and hence n → ∞ lim sin ( ( 2 + 3 ) n π + 6 1 π ) = sin 6 1 π = 2 1